New roles for diasporas in international relations - Cohen, R (University of Toronto Press, 2005)
Cohen’s essay reviews the recent volume edited by Hazel Smith and Paul Stares, Diasporas in Conflict: Peace-Makers or Peace-Wreckers (United Nations UP, 2007), even as it explores new developments concerning “the important role diasporas can play in the politics of their homelands,” an established topic in the study of diasporas and international relations. Cohen argues that although there are antecedents for such a role extending back to the Cold War and even earlier, the collapse of the Soviet Union and the decline of bipolar global politics, combined with the increasing importance of NGOs, has offered “diasporas an enhanced opportunity to intercede in the often precarious politics of their homeland states.” He explores and comments upon the empirical variations that emerge within the general categories and conclusions deployed by the contributors to Diasporas in Conflict, working on specific diasporas, and especially by the editors. There is, he shows, considerable latitude in these categories. Thus, it can be demonstrated that “shifts in the global opportunity structure will either accommodate diasporic interventions or inhibit them”; that “the contours of diasporic politics will vary according to whether the diaspora is stateless or state-linked”; and, finally, that “leaders of diasporas may be imbedded in dominant state structures or may seek to remain free of state influence.” It is not surprising, then, that—to return to the title of the book under discussion—diasporas can function, and have functioned, both as peace-makers and as peace-wreckers.